Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1021/ja9526170
|View full text |Cite
|
Sign up to set email alerts
|

Hydride Exchange Processes in the Coordination Sphere of Transition Metal Complexes:  The OsH3(BH4)(PR3)2 System

Abstract: The problem of intramolecular hydrogen atom exchange in the OsH3(BH4)(PR3)2 system is examined from both theoretical and experimental points of view, through ab initio MO calculations on the OsH3(BH4)(PH3)2 system at the MP2, MP4, and CCSD(T) computational levels and variable-temperature 1H NMR studies on the OsH3(BH4)(P i Pr3)2 complex. Three different exchange processes are fully characterized from a theoretical point of view through location of intermediates and transition states. Experimental results suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 59 publications
3
48
0
Order By: Relevance
“…Oxidative addition of H 2 to ruthenium (II) cyclopentadienyl phosphine complexes is known to form dihydride complexes such as ½RuCp à H 2 ðP i Pr 3 Þ 2 ½BAr F 4 [24]. Breaking a B-H bond and making a B-D bond (similar to the exchange process observed in borohydride complexes such as OsH 3 (g 2 -BH 4 )(PR 3 ) 2 [25]) effects H/D exchange. Reductive elimination of HD (g) would then afford (initially partially) deuterated 1. unable to generate an unsaturated species, which also has a coordinated borane -both being necessary for H/D exchange to occur.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative addition of H 2 to ruthenium (II) cyclopentadienyl phosphine complexes is known to form dihydride complexes such as ½RuCp à H 2 ðP i Pr 3 Þ 2 ½BAr F 4 [24]. Breaking a B-H bond and making a B-D bond (similar to the exchange process observed in borohydride complexes such as OsH 3 (g 2 -BH 4 )(PR 3 ) 2 [25]) effects H/D exchange. Reductive elimination of HD (g) would then afford (initially partially) deuterated 1. unable to generate an unsaturated species, which also has a coordinated borane -both being necessary for H/D exchange to occur.…”
Section: Resultsmentioning
confidence: 99%
“…Eisenstein et al [21] and Lledó s et al [44] have noted that these complexes are stabilized by electron donation to the metal atom from the B-H r orbital and back donation of electron density from the metal atom to a p p orbital. Therefore, even if there is strong back-bonding, breaking of B-H bond should not be expected.…”
Section: Introductionmentioning
confidence: 99%
“…17 Hz), a typical value for | 2 J PC | between mutually cis isonitrile and phosphine ligands. 34 Both the chemical shifts and the broadening of the resonance for the metal-bonded carbon atom (caused by the quadrupolar 14 N nucleus) are characteristic for ruthenium(II) complexes containing the ligand Me 3 CNC. 35 The patterns of resonances in the 1 H and 13 C NMR spectra for the propanoyl ligand in 5c were similar to those for 5a and 5b.…”
Section: (Iii) Reaction Of 3 With Me 3 Cnc: Early Stagesmentioning
confidence: 99%
“…3,4 The most generally accepted mechanism, however, is that which involves the initial breaking of an M • • • HB bridge, and molecular orbital calculations have indicated that this is the preferred pathway for exchange of bridging and terminal hydrogens in the tetrahydroborate ligand in [Os(g 2 -BH 4 )H 3 {P(CHMe 2 ) 3 } 2 ]. 14 In their early review of tetrahydroborate complexes, Marks and Kolb 15 noted that the apparent ease with which an M • • • HB bridge could be broken meant that a vacant coordination site could be created on the metal with very little expenditure of energy, and suggested that this meant that tetrahydroborate complexes could play an important role in catalysis, since the vacant coordination site could allow attachment of a substrate to the metal. Additionally, a site which became vacant at any stage in a catalytic cycle could be protected by the reclosing of the M • • • HB bridge.…”
Section: Introductionmentioning
confidence: 99%